WORKING CAPITAL MANAGEMENT AND THE FINANCIAL PERFORMANCE OF CONSUMER GOODS MANUFACTURING COMPANIES IN NIGERIA - CECILIA ADURAYEMI ADU; OLUTAYO OWOLABI SOYOYE (International Studies Journal)
The study examined the effect of working capital management and the profitability of consumer goods manufacturing companies in Nigeria. Other objective of this study was to determine the effect of inventory turnover on return on investments. The population of this study comprised twenty-four consumer goods firms listed on the Stock Exchange Group as at 2021. Purposive sampling technique was adopted by the study to select ten listed consumer goods firms that have adequate information. The source of data for this study data was secondary obtained from the published audited annual reports of consumer goods firms especially the income statement and statement of financial position for a period of ten years from 2013 to 2022. The regression analytical method was adopted for this study and it was found out that inventory turnover had a positive relationship with return on investment (ROI) of consumer goods firm as indicated by a regression co-efficient of -0.000872 and this relationship was statistically significant at 5% level with a probability value of 0.8007. It was suggested that management of organizations should make sure that there is development of adequate or sufficient and efficient working capital policy for the organizations.